2021
DOI: 10.1186/s13756-021-00936-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mechanisms and correlated risk factors of antimicrobial-resistant ESKAPEE pathogens isolated in a tertiary hospital in Malaysia

Abstract: Background Knowledge on the epidemiology, genotypic and phenotypic features of antimicrobial-resistant (AMR) ESKAPEE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp., and Escherichia coli) and their association with hospital-acquired infections (HAIs) are limited in Malaysia. Therefore, we evaluated the AMR features and resistance mechanisms of the ESKAPEE pathogens collected in a tertiary hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Among all the ESKAPE pathogens, OXA was highly prevalent on the chromosomes of A. baumannii (~1.5 copies) per genome, followed by P. aeruginosa and K. pneumoniae . Our results exhibited complete concordance with a recent study, which also reported presence of a large number of blaOXAs in A. baumannii, K. pneumoniae and P. aeruginosa [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…Among all the ESKAPE pathogens, OXA was highly prevalent on the chromosomes of A. baumannii (~1.5 copies) per genome, followed by P. aeruginosa and K. pneumoniae . Our results exhibited complete concordance with a recent study, which also reported presence of a large number of blaOXAs in A. baumannii, K. pneumoniae and P. aeruginosa [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…Many studies have focused specifically on the Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , Enterobacter spp., and Escherichia coli pathogens that are highly resistant to last-resort drugs and extensively described in different microbial reservoirs [9] . Additionally, MRSA has been reported to be both human- and animal-associated with a high risk for zoonotic transmission 10 , 11 .…”
Section: Microbial Reservoirs Of Antimicrobial Resistancementioning
confidence: 99%
“…Multi-drug resistant Enterobacterales strains are one of the greatest public health threats, often causing severe infections, such as bloodstream infections, pneumoniae, and abdominal infections. 14,20 However, data from Shanxi in patients infected with MDR-E is scarce, and the available literature has revealed the risk factors of Gram-negative bacteria infection. Therefore, we reported the mortality risk factors of the patients infected with MDRE pathogens isolated from a tertiary hospital located in Shanxi, China.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] The most encountered ESBL genes among E. coli and KP are blaTEM, blaSHV, and blaCTXM. 20 One study from the Netherlands showed that from 1990 to 2015, fecal colonization rates of ESBL-producing Enterobacterales were estimated to be 14% in healthy populations, increasing by about 5% per year. 21 Moreover, MDRE strains could carry three or more resistance genes and have a broader spectrum of drug resistance than CRE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation